2012
DOI: 10.1128/aac.05412-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Antileishmanial Leads from Hits Obtained by High-Throughput Screening

Abstract: A previous screen of ϳ200,000 compounds from the PubChem database identified 70 compounds possessing 50% effective concentrations (EC 50 s) below 1 M against Leishmania major promastigotes that were not toxic to mammalian epithelial cancer cells at this concentration (E. Combinations of existing antileishmanial drugs have also been studied. Different combinations of treatment with single-dose liposomal amphotericin B followed by short courses of miltefosine were extremely effective, with a single dose of lipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…FICs were used for constructing the isobolograms, with the sum of the FICs (⌺FICs) being equal to the FIC of DB766 plus the FIC of posaconazole, thus allowing the determination of the nature of the DB766-posaconazole interaction. The susceptibility of intracellular ␤-lactamase-expressing L. donovani to DB766, posaconazole, and fixed-ratio combinations of these two compounds was determined as outlined previously (13). FIC, ⌺FIC, and mean ⌺FIC values were calculated as described above for L. donovani axenic amastigotes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FICs were used for constructing the isobolograms, with the sum of the FICs (⌺FICs) being equal to the FIC of DB766 plus the FIC of posaconazole, thus allowing the determination of the nature of the DB766-posaconazole interaction. The susceptibility of intracellular ␤-lactamase-expressing L. donovani to DB766, posaconazole, and fixed-ratio combinations of these two compounds was determined as outlined previously (13). FIC, ⌺FIC, and mean ⌺FIC values were calculated as described above for L. donovani axenic amastigotes.…”
Section: Methodsmentioning
confidence: 99%
“…Leishmania donovani MHOM/SD/62/ 1S-CL2 D promastigotes were adapted to axenic amastigote forms by culturing the former at 37°C in a humidified 5% CO 2 atmosphere in axenic amastigote medium as described previously (12). For intracellular assays, ␤-lactamase-expressing L. donovani promastigotes (provided by Frederick Buckner, University of Washington) were maintained as outlined earlier (13). Wild-type and CYP5122A1 half-knockout (HKO) promastigotes of L. donovani MHOM/IN/80/DD8 (14) were used in DB766 and ketoconazole susceptibility assays.…”
Section: Methodsmentioning
confidence: 99%
“…The potency of AIAs and control compounds for VL (amphotericin B) and for CD (Bz) against intracellular L. amazonensis and L. donovani and bloodstream trypomastigotes and amastigotes of T. cruzi strain Y was determined as follows. Intracellular Leishmania assays were conducted as described previously for L. donovani (29) and L. amazonensis (13). For the analysis of the effects of the compounds upon bloodstream trypomastigote forms, 5 ϫ 10 6 /ml parasites were incubated for 24 h at 37°C in RPMI 1640 medium supplemented with 10% fetal calf serum in the presence or absence of serial dilutions of each compound.…”
Section: Aiasmentioning
confidence: 99%
“…In this regard, we note that de Muylder and others have recently compared the frequency of in vitro hits by using promastigotes, axenic amastigotes, and within-macrophage amastigotes for 909 compounds, 8 and a publication by Zhu and others is also now available. 9 The in vitro experience of de Muylder and others suggested that screening against the promastigote stage of L. donovani, although more suitable for automation, fails to identify all active compounds and leads to numerous false-positive hits. 8 In vivo evaluation of potential oral agents for CL agents.…”
Section: Drug Discovery Algorithmmentioning
confidence: 99%